Design and Development of SDR System using PHP and HTML - Chung, Shue Li; Mostafa, Salama A. (Applied Information Technology And Computer Science, 2023)
Research Management Centre (RMC) UTHM manages and enhances all the research cultures and activities in the university. The purpose to develop the Scientific Data Repository (SDR), a web-based scientific data repository, is to provide a platform of research data management and archives. The system allows RMC to manage the research data and the researchers can donate or request the research data. This system is developed using C# programming language and based on Prototyping methodology. State the user and modules in the system… Therefore, this system can assist RMC to organize the research data more efficiently and help the researchers to obtain the data they need.